Design and development of interactive textiles for impact detection and use with an automated boxing scoring system - Helmer, R. J. N.; Hahn, A. G.; Staynes, L. M.; Denning, R. J.; Krajewski, A.; Blanchonette, I. (Procedia Engineering, 2010)
This project was aimed at delivering a cost-effective, manufacturable and well characterised vest for impact detection, to support hdevelopment of an automated scoring system for amateur boxing. The initial work focused on partial automation of the manufacture of an existing boxing vest design to increase the vest's robustness and allow small scale manufacture. The multiplication of the existing sensor vest enabled routine use in field trials that assisted the development of the related hardware and software but involved a wide combination of time consuming manufacture skills with a high labour component. Parallel work explored the use of alternative vest impact sensing methods incorporating textile sensors with a view to increasing garment functionality and achieving a more [`]singlet-like' structure. This resulted in the development of a new [`]all-textile' sensor vest that has significant advantages in terms of practicality, impact discrimination, and manufacture.